1995
DOI: 10.1111/j.1365-2885.1995.tb00583.x
|View full text |Cite
|
Sign up to set email alerts
|

A non‐invasive and quantitative method for the study of tissue injury caused by intramuscular injection of drugs in horses

Abstract: The present study was undertaken to measure the weight of muscle destroyed by an intramuscular injection of phenylbutazone (PBZ) in horses. In six horses, CK disposition parameters were evaluated after intravenous (i.v.) and intramuscular (i.m.) administration of a CK horse preparation. The same horses received PBZ, a potentially irritating agent, by i.v. and i.m. (neck and hindquarter) routes. Data were analysed using compartmental approaches and instantaneous CK flux was calculated using a discrete deconvolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…injections of irritating drugs [24,25]. Becker et al [3] reported that sulphadoxine-trimethoprim caused a marked increase of CK after s.c. administration: the increase was about 20% of that caused by i.m.…”
Section: Discussionmentioning
confidence: 99%
“…injections of irritating drugs [24,25]. Becker et al [3] reported that sulphadoxine-trimethoprim caused a marked increase of CK after s.c. administration: the increase was about 20% of that caused by i.m.…”
Section: Discussionmentioning
confidence: 99%
“…and im. administration and a plasma terminal half-life of 112 ± 18 min and 11.8 ± 5.3 h, respectively [122]. …”
Section: Drug Examplesmentioning
confidence: 99%
“…Creatine kinase has been shown to be reliable indicator of tissue damage (Steiness et al 1978;Toutain et al 1995). injection were monitored clinically and by determination of serum creatine kinase (CK) activity.…”
Section: Analysis Of Tissue Irritationmentioning
confidence: 99%